(untitled) (Archives of Pediatrics of Uruguay, 2020)
Introduction: pediatricians have an essential role in managing children with chronic respiratory disorders. Consultation with specialists is necessary in specific cases of uncertain diagnoses or in difficult to treat or severe cases. Protocol devising or training teams enable the selection of those requiring specialist care. Based on these criteria, a Pediatric Pneumology Reception Committee (PPRC) was created at a comprehensive health care provider in Montevideo. Objective: to describe the PPRC experience from 10/1/2017 to 09/30/2018 Materials and methods: descriptive, retrospective study. Variables: age, sex, growth, reason for consultation, diagnosis, severity, death risk factors, comorbidities, vaccines, behavioral response, hospitalizations before and after intervention of the PPRC. Results: 306 children received care: 84% had asthma, 16% recurrent wheezing. 16% were <3 years, 53% from 3 to 9 years of age, and 31% >10 years of age. 21% had co-morbidities, with a predominance of recurrent wheezing (p<0,05). 18.5% were overweight or obese. The reason for consultation was a regular check-up in 50% of the cases, diagnostic uncertainty in 20% and therapeutic difficulties in 30%. A significant association between severe asthma and obesity was found (p<0,05). 3% were sent to pediatric pneumologists and 35% to the educational outpatient clinic. 32% had been hospitalized: 30% before consulting the PPRC and 2% afterwards (p<0.05). Conclusions: highly prevalent pathologies, such as asthma and recurrent wheezing are the main causes of referrals to pneumologists. The PRCP contributed to a comprehensive approach to these patients and to more rational referrals to specialists.